Molecular phenotyping of plant single cell-types enhances forward genetic analyses - Schiefelbein, John (Frontiers in Plant Science, 2015)
Recent advances in the isolation of single cell-types in plants provides an opportunity to conduct detailed analyses of their molecular characteristics at high resolution. This kind of cell-type specific molecular phenotyping is likely to enhance forward genetics studies to dissect the effect of mutations and thereby aid gene function assignment. Recent experimental results support this view, demonstrating that different cell types exhibit substantial variation in transcript, protein, and metabolite accumulation and these molecular phenotypes are often sensitive to genetic and environmental alterations. The use of single cell-type molecular phenotyping approach to define plant gene function is most amenable to cell types with well-characterized molecular tools and isolation protocols.